Defense and conditions for the non-application of the law of the food chain to the deliveries of products from partners to cooperatives (first and second degree), to other associative entities and those made under inter-cooperative agreements - Vargas Vasserot, Carlos (REVESCO. Revista de Estudios Cooperativos, 2023)
This paper aims to analyze the effects produced by the recent legal amendment of Law 12/2013, which regulates different measures to improve the food chain in cooperatives as well as in other associative entities. Firstly, it will be developed the origin and evolution of the aforementioned Act. On top of that, it will be discussed the legal reform carried out by Law 16/2021, which among others, imposes the obligation of establishing individualized written food contracts for the deliveries made by their partners. Secondly, it is argued that due to the legal nature of the cooperative activity, the food chain law should not be applied at any point. Even so, this will also be underlined by taking into account the specific legal support cooperative activity has, such as its internal, corporate, non-profit, and non-commercial nature. Thirdly, the paper deal with the situation regarding this law that affects second and subsequentdegree cooperatives, agrarian transformation companies, capital companies majority-owned by cooperatives, as well as the study of the operations carried out under inter-cooperative agreements. Finally, a critical analysis is made of the provision that establishes the requirements for cooperatives and other associative entities to avoid the obligation to contractually articulate the deliveries of their members' products. Viable solutions or recommendations that these entities, statutorily or by social agreements should establish, will be discussed. To name just but a few examples, it will be developed the procedure for determining the value of the product delivered by its partners or the settlement schedule.
Keywords: Food chain; Agri-food cooperatives; Inter-cooperative agreements; Agricultural contracts; Cooperative activity; Cooperative act; Organization of producers; Agrarian transformation companies; Cooperative integration; Effective cost; Prices